Acute ingestion of beetroot juice does not improve short-duration repeated sprint running performance in male team sport athletes - Reynolds, C. M. E.; Evans, M.; Halpenny, C.; Hughes, C.; Jordan, S.; Quinn, A.; Hone, M.; Egan, B. (Journal of Sports Sciences, 2020)
The effects of acute ingestion of nitrate on short-duration repeated sprint performance (RSP) are unclear. This study investigated the effect of acute ingestion of beetroot juice on a test of RSP in team sport athletes. Sixteen male team sport athletes undertook four trials using a 40 m maximum shuttle run test (MST), which incorporates 10 × 40 m shuttle sprints with 30 s between the start of each sprint. Two familiarisation trials, followed by nitrate-rich beetroot juice (BR; ~6 mmol nitrate) and nitrate-depleted beetroot juice (PLA; ~0.0034 mmol nitrate) trials were completed in a randomised, double-blind manner. Ingestion of beetroot juice 3 h prior to exercise elevated plasma nitrate concentrations ~6-fold in BR (BR, 413 ± 56 µM; PLA, 69 ± 30 µM; P < 0.001). RSP, assessed by sprint performance decrement (Sdec; %), did not differ (P = 0.337) between BR (5.31 ± 2.49%) and PLA (5.71 ± 2.61%). There was no difference between trials for total sprint time (P = 0.806), fastest sprint (P = 0.341), slowest sprint (P = 0.787), or post-exercise blood lactate concentration (BR, 11.8 ± 2.5 mM; PLA, 12.2 ± 2.3 mM; P = 0.109). Therefore, acute ingestion of beetroot juice did not improve a test of short-duration RSP in team sport athletes.